Stylistic characters of shophouse in Bentong, Pahang / Muhammad Faris Alias and Tengku Anis Qarihah - Alias, Muhammad Faris; Qarihah, Tengku Anis (College of Built Environment, 2023)
Shophouse is a common urban building typology found in Southeast Asia and China, consists of commercial use on the ground floor and residential on the top floor.